Some transformations and physicochemical properties of new S-substituted 5-thiophene-(3-ylmethyl)-4R-1,2,4-triazole-3-thiols - A. V. Khilkovets (The State Expert Center of the Ministry of Health of Ukraine, 2021)
Nitrogen-containing heterocyclic compounds are widely represented in modern organic chemistry. A special place among the huge number of substances presented is occupied by derivatives of 1,2,4-triazole due to their uniqueness and prospects. In recent years, these derivatives have remained the object of close attention of both synthetic chemists and researchers engaged in the search for new biologically active substances of a wide spectrum of action, the synthesis of optical materials, dyes, corrosion inhibitors, veterinary drugs, etc. It is known from the literature that the combination of the aromatic heterocycle of thiophene and 1,2,4-triazole is a promising area for research. The result of such combinations is a number of compounds obtained with fairly high yields and a wide range of activities. Thus, further chemical modification of 1,2,4-triazole derivatives by additional administration of a typical thiophene pharmacophore is an urgent task. The aim of the study is to obtain new compounds in a number of S-substituted 5-thiophene-(3-ylmethyl)-4R-1,2,4-triazole-3-thiols and study their physico-chemical properties using complex analysis methods. The study of the physical and chemical properties of the compounds obtained was carried out according to methods that meet the standards of the state pharmacopoeia of Ukraine. The synthesis of new compounds was carried out according to generally accepted methods. The previously obtained 5-thiophene-(3-ylmethyl)-4h-1,2,4-triazole-3-thiol and 5-thiophene-(3-ylmethyl)-4-phenyl-1,2,4-triazole-3-thiol were used as starting compounds. Preparation of thioethanones was performed in an alkaline medium in the presence of methanol. The acids were obtained in an alcohol-alkaline medium with the addition of monochloroacetic acid. To obtain esters, two conventional methods were used. The first method is based on the alkylation in an alkaline-alcohol medium of the starting thiols with isopropyl ester of monochloroacetic acid. The second method is the classical esterification reaction. To confirm the structure and study of the physical and chemical properties, all the resulting compounds were crystallized. As a result, some new compounds that were not previously described were obtained, namely: thioethanones, thioacetamides, thioacetic acids, thioacetates, and a number of other thiopo-derivatives of these initial compounds. The structure and individuality of the obtained molecules were confirmed by elemental analysis (CHNS), IR and 1H NMR spectra. A number of new S-derivatives of 5-thiophene-(3-ylmethyl)-4R-1,2,4-triazole-3-thiols have been obtained. The physical and chemical properties of the obtained compounds are determined and their structure is confirmed using modern analysis methods. Some compounds will be transferred for further research.